Pemberdayaan Masyarakat Tani melalui Pengembangan Produk Olahan Ikan di Nagari Tarung-tarung, Kecamatan Rao, Kabupaten Pasaman, Sumatera Barat - Delvi Yanti; Deivy Andhika Permata (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
The aims of this activity of KKN-PPM (Community Development Services-Community Empowerment Study) are; 1) To obtain the method of fresh fish processing to be processed fish products (fish meatball, nugget, and crack); 2) To obtain the method of processed fish product packaging (fish meatball, nugget, and crack); 3) To obtain the ready marketed packaging of processed fish products (fish meatball, nugget, and crack) so that the community derives the benefits and increase their incomes; and 4) To form the sustainability of processed fish product centre (fish meatball, nugget, and crack). The method that has been applied was participation and action that involved targeted group of community, and the students were utilized as facilitators. Participants in this activity consist of 30 students and collaborate with farmer group of Sejahtera Bersama with members of 25 persons. The result that had been obtained in this activity was the community (farmer group of Sejahtera Bersama) understand the method of processing and packaging of processed fish product, and the group of partners have succeeded in making processed fish products in packaging that is ready to be marketed. From the t-test pairs, statistically, there is significant differerent between average of student soft skill before and after the activity of of KKN-PPM (Community Development Services-Community Empowerement Study), with remark sig.(2-tailed) 0.000< 0.05 level of significant (α).